CHANGES IN MORPHOMETRIC PARAMETERS OF COLLAGEN FIBER BUNDLES OF THE ADRENAL CAPSULE IN RATS WITH THYROTOXICOSIS OF THE CONTROL AND EXPERIMENTAL GROUPS - Bakhtiyor S. Umarkulov; Gulbahor A. Umarkulova (Central Asian Journal of Medicine, 2025)
The thyroid gland acts directly on the adrenal glands through its hormones. An excess of thyroid hormones leads to a change in the function of the adrenal glands. In rats, when modeling thyrotoxicosis, the adrenal capsule was significantly thickened in all areas compared with the control. This indicator indicated a partial recovery of the capsule during treatment with mercazolil, and a slight improvement in the thickness of the adrenal capsule during treatment with mercazolil and olive oil. In rats with thyrotoxicosis, the bundles of collagen fibers in the adrenal capsule were significantly thickened in all areas compared to the control group, and with traditional and non-traditional treatment they were significantly thinner than in rats with the thyrotoxicosis model. In the group with thyrotoxicosis and in the group where the rats received olive oil with mercazolil, recovery was faster.